Growth and productivity of sesame (Sesamum indicum) as influenced by intercropping with mungbean (Vigna radiata) and sulphur fertilization - Prajapat, K.; Shivran, A.C.; Choudhary, G.L.; Kumawat, Sita (Annals of Agricultural Research, 2014)
A field experiment was conducted during kharif season of 2009-10 at Agronomy farm of S.K.N. College of Agriculture, Jobner, Jaipur, comprising 20 treatment combinations of 5 intercropping systems viz., sole mungbean 'RMG- 268', sole sesame 'RT-127', mungbean + sesame in 2:1 row ratio, mungbean + sesame in 3:1 row ratio and mungbean + sesame in 4:1 row ratio and 4 sulphur levels viz., 0, 15, 30 and 45 kg S/ ha. Treatments were tested in randomized block design with three replications.Intercropping system brought about significant differences in the mungbean equivalent yield (MEY) and LER (Table 1). The sole mungbean, being at par to 4:1 row ratio, recorded significantly higher MEY (1207 kg/ha), while mungbean+sesame (4:1) gave significantly highest LER (1.07) as compared to all other row patterns. Based on the results, it may beconcluded that sole mungbean and mungbean+sesame (4:1) gave statistically similar MEY, so intercropping of sesame and mungbeancan be taken for fulfilment the requirement of both oil seed as well as pulse.